A note on the Occurrence of Fresh Water Ostracods in the Siwalik Group of Surai Khola Section, Western Nepal (Journal of Nepal Geological Society, 1995)
The occurrence of fresh water ostracodes-Candona lactea Baird, Cypria ophthalmica (Jurine), Cyprinotus sp., Jlyocypris gibba (Ramdohr),  Limnocythere sp., and  Potamocypris sp- is  recorded  from the Siwalik Group of Surai Khola Section, southeast of Dang in West Nepal.